Real-Time PCR Validation for Mycobacterium tuberculosis Complex Detection Targeting IS6110 Directly From Bovine Lymph Nodes - Sánchez-Carvajal, José María; Galán-Relaño, Ángela; Ruedas-Torres, Inés; Jurado-Martos, Francisco; Larenas-Muñoz, Fernanda; Vera, Eduardo; Gómez-Gascón, Lidia; Cardoso-Toset, Fernando; Rodríguez-Gómez, Irene Magdalena; Maldonado, Alfonso; Carrasco, Librado; Tarradas, Carmen; et al. (Frontiers in Veterinary Science, 2021)
Rapid and accurate diagnostic tools, such as qPCR, need to be implemented as confirmatory test in the framework of bovine tuberculosis (bTB) surveillance and control programs, shortening the turnaround time to confirm bTB infection. The present study aimed to evaluate a direct qPCR from fresh tissue samples targeting the insertion sequence IS6110 using individually homogenised bovine lymph nodes compared to microbiological culture. Retropharyngeal, tracheobronchial and mesenteric lymph nodes fresh tissue samples (n=687) were collected from 230 different cattle carcases at the slaughterhouse. Only 26 out of the 230 examined animals showed tuberculosis-like lesions (TBL) with 62 out of 230 considered as true positive. Among these 62 animals, 61 resulted as culture-positive, whereas 48 were qPCR-positive. Thus, this qPCR targeting IS6110 showed corrected diagnostic sensitivity and specificity values of 77.4% (95% CI: 67-87.8%) and 100% (95% CI: 100-100%), respectively, and a positive-predictive-value (PPV) of 100% (95% CI: 100-100%) and negative-predictive-value (NPV) of 92.3 % (95% CI: 88.4-96.2%). Positive and negative-likelihood-ratio (PLR and NLR) were 100.2 and 0.2, respectively, and the agreement between microbiological culture and this qPCR was almost perfect (κ=0.83). These results highlight this qPCR targeting IS6110 as a suitable complementary method to confirm bTB in animals with either TBL or NTBL, decreasing the number of samples subjected to microbiological culture and, hence, its overall associated costs and the turnaround time (under 48 hours) to confirm bTB infection. Besides, sampling mesenteric lymph node, which is uncommonly sampled, together with tracheobronchial and retropharyngeal ones, is advisable during post-mortem inspection in bTB surveillance programs at the slaughterhouse, especially in areas with a low bTB prevalence scenario.